COPD, emphysema and the onset of lung cancer. A systematic review. Issue 2 (28th November 2016) - Mouronte-Roibás, Cecilia; Leiro-Fernández, Virginia; Fernández-Villar, Alberto; Botana-Rial, Maribel; Ramos-Hernández, Cristina; Ruano-Ravina, Alberto
Highlights: COPD and emphysema seem to increase the risk of developing lung cancer. This risk is higher for smokers with heavier tobacco consumption. COPD and emphysema share some underlying pathophysiologic mechanisms. Spirometries in smokers might help to select patients at higher risk of developing lung cancer. Abstract: Chronic Obstructive Pulmonary Disease (COPD) and emphysema have been described as possible risk factors for lung cancer. We aim to assess the relationship between COPD, emphysema and the onset of lung cancer. We have developed a systematic review of the published literature in order to systematically analyze the scientific evidence available on this association, applying predefined inclusion and exclusion criteria. 11 Studies were included. Both COPD and emphysema seem to increase the risk of developing lung cancer, being this risk higher for smokers with heavier tobacco consumption. These results emphasize the need for physicians to perform spirometries in current and former smokers and lung image tests when needed in order to identify COPD and emphysema and thus select patients at higher risk of developing lung cancer.